SIMILARITIES AND DIFFERENCES OF GRAMMATICAL CATEGORY PERSON IN TWO DIFFERENT LANGUAGES - Umarova Asemnur Akadilovna (PEDAGOGS, 2024)
Annotation: This article compares and contrasts the grammatical category of person in English and Uzbek languages. It highlights similarities such as the recognition of first, second, and third persons, while also delving into differences such as pronoun usage, formality distinctions, and verb conjugation. The analysis explores cultural and linguistic implications, shedding light on how language reflects societal norms and values.